COMPLIANCE OF MULTI DRUG THERAPY (GOVERNMENT PROGRAMS) IN LEPROSY AT PUSKESMAS KAMONJI PALU CITY - Rahman, Abd; Napirah, Muh Ryman; Musdalipa, Musdalipa (Preventif : Jurnal Kesehatan Masyarakat, 2018)
Background & Objective: Recently, disease leprosy is still a health problem in Indonesia with a very high prevalence, i.e. 17.025 cases. The objective of this research was to find out the relationship between knowledge, attitude, family support, and health workers performance toward medication adherence. Material and Method: This research was analytic survey with cross sectional approach, then sampling technique is done by total sampling, i.e. 46 lepers. Data analyzed analytically included univariate and bivariate analysis, at the level of 95%. Result: Chi square test describe that there was a relationship between knowledge (p = 0.002), attitude (p = 0.000), family support (p = 0.001), and the role of health workers (p = 0.004), with the medication adherence. Regular treatment is very important for the lepers to get the cure.. Conclusion: Knowledge, attitude, family support, and the role of health workers have a significant relationship with the medication adherence.